Characteristics of hydrothermally synthesized SnS2 for thin film use - Junaidu, Mustapha Hassan; Liew, Josephine Ying Chyi; Onimisi, Muhammad Y.; Tafida, Rabiu Abubakar; Bello, Musa; Adezuka, Yahaya; Owolabi, Joshua Adeyemi; Lawal, H.A. (Springer Nature, 2024)
Tin disulfide (SnS2) nanoparticles were synthesized via hydrothermal process and were deposited as ultrathin layer (27.5 nm) onto SLG via vacuum thermal evaporation. The SnS2 nanoparticles were characterized for their structural, purity, chemical, morphological, optical and electrical properties. The XRD patterns and the Raman spectra confirmed the successful synthesis of SnS2 nanoparticles. The stoichiometry and leaf like structure obtained from EDS and FESEM analysis of the SnS2 nanoparticles further proved its formation. The ultrathin layer deposited and annealed at 300 °C for 1 h showed XRD patterns of hexagonal structured SnS2 with crystallinity of 57.7 nm, bandgap energy of 2.7 eV and resistivity of 0.65 Ω cm.